1983
DOI: 10.1177/009318538301100403
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Custody Agreements: Joint versus Sole Legal Custody

Abstract: The public records of 500 divorces involving minor children were abstracted from the files of a county probate and family court. The families’ demographics and the chronology of the marriages and their dissolution are reported, as are the varieties and frequencies of the custody and visitation decisions. The provisions made for the children's current and future physical, financial, and educational needs are summarized together with the incidences of post-divorce litigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…Joint legal custody is more likely among parents who file for divorce rapidly upon separation or who file under a no-fault provision (Arditti, 1992;Koel et al, 1988;Phear et al, 1983), and more likely in mediation rather than an adversarial process (Pearson, 1991). Conversely, in one study that observes quality of the parental relationship, frequent disagreement is positively associated with the likelihood of joint legal custody (Seltzer, 1998), perhaps because both parents are trying to ensure their perspectives on child-rearing is considered.…”
Section: Theoretical Framework For Legal Custodymentioning
confidence: 99%
See 2 more Smart Citations
“…Joint legal custody is more likely among parents who file for divorce rapidly upon separation or who file under a no-fault provision (Arditti, 1992;Koel et al, 1988;Phear et al, 1983), and more likely in mediation rather than an adversarial process (Pearson, 1991). Conversely, in one study that observes quality of the parental relationship, frequent disagreement is positively associated with the likelihood of joint legal custody (Seltzer, 1998), perhaps because both parents are trying to ensure their perspectives on child-rearing is considered.…”
Section: Theoretical Framework For Legal Custodymentioning
confidence: 99%
“…For example, after couples separated and before a custodial decision was made, fathers who were later awarded joint legal custody spent more overnights with their children (Albiston et al, 1990). This theoretical reasoning may explain the empirical finding that joint legal custody is more common among parents who have been married (and thus have been living with their children) for a long time (Arditti, 1992;Huang et al, 2003;Koel et al, 1988;Phear et al, 1983). However, the evidence is mixed.…”
Section: Theoretical Framework For Legal Custodymentioning
confidence: 99%
See 1 more Smart Citation
“…In at least some cases, the content of joint legal custody arrangements is essentially the same as that found in those made under sole custody awards. While joint legal custody has become relatively common (30% of all custody awards in one study), joint physical custody is quite rare, constituting under 2% of all awards (24).…”
Section: Current Researchmentioning
confidence: 99%
“…A firm belief that the other parent was both competent and important to the child reappears consistently as does the need and ability to be flexible (1, 2, 20, 31, 37). Other variables frequently associated with successful coparenting under joint legal custody include geographic proximity (1, 37), relatively high compliance with child‐support awards (14, 22), and a relatively low level of relitigation (3, 11, 19, 22), though one study by Phear and colleagues (24) found no significant relationship between joint versus sole custody on this variable.…”
Section: Current Researchmentioning
confidence: 99%